2008
DOI: 10.1111/j.1365-2885.2008.00942.x
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine‐induced hyperactivity in the horse: comparisons of drug and metabolite concentrations in blood and cerebrospinal fluid

Abstract: The goals of this study were to elucidate the temporal and quantitative relationships between caffeine and its major bioactive metabolites in blood and cerebrospinal fluid (CSF) and to characterize the pharmacokinetic-pharmacodynamic relationship for caffeine-induced changes in spontaneous locomotor activity in the horse. We hypothesized that caffeine and its metabolites distribute efficiently into the CSF to antagonize adenosine A1 and A2a receptors and that spontaneous locomotor activity correlates well with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 23 publications
3
4
0
Order By: Relevance
“…Similar results were also observed by Vickroy et al [29], who reported an increase in motor activity in horses with plasma caffeine concentrations of 4,000 ng/ml. Therefore, the clinical signs observed in the horses participating in this study (compulsive walking, mydriasis, congested ocular mucosa and episcleral vessels and intense sweating) may reflect the high plasma concentrations of caffeine (51,564 ± 5,708 ng/ml) observed at T56.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar results were also observed by Vickroy et al [29], who reported an increase in motor activity in horses with plasma caffeine concentrations of 4,000 ng/ml. Therefore, the clinical signs observed in the horses participating in this study (compulsive walking, mydriasis, congested ocular mucosa and episcleral vessels and intense sweating) may reflect the high plasma concentrations of caffeine (51,564 ± 5,708 ng/ml) observed at T56.…”
Section: Discussionsupporting
confidence: 91%
“…The bioavailability of caffeine in horses after oral administration was 39% [ 28 ], and as the total average caffeine consumption by the animals in the present study was 78 mg per kilogram of body weight (mg/kg BW), therefore, on average, approximately 30 mg/kg BW of caffeine were absorbed by the animals over 56 h. Behavioral changes occur in horses when plasma caffeine concentrations are greater than 2,000 ng/ml [ 11 ]. Similar results were also observed by Vickroy et al [ 29 ], who reported an increase in motor activity in horses with plasma caffeine concentrations of 4,000 ng/ml. Therefore, the clinical signs observed in the horses participating in this study (compulsive walking, mydriasis, congested ocular mucosa and episcleral vessels and intense sweating) may reflect the high plasma concentrations of caffeine (51,564 ± 5,708 ng/ml) observed at T56.…”
Section: Discussionsupporting
confidence: 91%
“…In vitro studies show that the minimal inhibitory concentration of cafeine at these receptors is about 1 µM (194 ng/ml). As reported by Vickroy et al, 24 the concentration of cafeine in the blood and the cerebrospinal luid highly correlates in horses and shows a concentration ratio of 0.87. In addition, they report a strong correlation between the efect of cafeine on the motor activity of horses and the concentration of cafeine in the cerebrospinal luid, which can be used as a reasonable indicator of the actual concentration of cafeine in the brain.…”
Section: Discussionsupporting
confidence: 57%
“…In horses, microdialysis has been used in pharmacokinetic studies and for assessment of muscle energy metabolism (Chou et al, 2001;Edner et al, 2005Edner et al, , 2009Ingvastlarsson et al, 1992;Murchie et al, 2006;Vickroy et al, 2008). Lamellar microdialysis has been described for pharmacokinetic studies (Nourian et al, 2010a, b).…”
Section: Introductionmentioning
confidence: 99%